(untitled) (Mediscope, 2025)
Background and objective: Dermatophytosis or tinea infection is one of the most commonly encountered diseases in day-to-day clinical practice. Appropriate use of drugs is essential in dermatophytosis to reduce morbidity and the associated financial burden to the sufferers. This study aims to analyze the pattern of drug prescription in dermatophytosis in the Southern region of Bangladesh. Methods: A cross-sectional study was conducted from July 2024 to December 2024 in the outpatient department (OPD) of skin and venereal diseases (Skin & VD) at Gazi Medical College Hospital (GMCH), Khulna, and three private practice chambers in Khulna, Narail and Gopalganj districts. A total of 370 patients of all age groups and both genders were included in the study. Data regarding demographics, clinical features, pharmacotherapy, and prescribing indicators were recorded and analyzed. Results: Among the total 370 dermatophytosis cases, there were 174 males and 196 females. The majority of the respondents belonged to the age groups of 16-30 years and 31-40 years, each consisting of 121 (32.7%) patients. Tinea corporis (28.6%) was the prominent clinical type of single-site infection. Among single topical agents, the most commonly prescribed drug was Luliconazole (29.5%). Itraconazole (55.1%) was the most commonly used oral formulation. Analysis of the 370 prescriptions also showed that the average number of drugs prescribed per encounter was 3.74, and the average number of antifungals prescribed per encounter was 2.06. Conclusion: This study provides key information regarding the drug utilization pattern in the treatment of dermatophytosis. Appropriate steps should be taken to develop a rational and uniform treatment guideline to minimize the disease burden in society. Mediscope 2025;12(2): 72-78